A Detailed Morphological and Spectroscopic Study of Merging Dwarf Galaxy PGC 030133 - Chhatkuli, D.N.; Paudel, S.; Aryal, B. (Journal of Nepal Physical Society, 2021)
We present a detailed morphology and spectroscopic study of a merging dwarf galaxy PGC 030133. Using the publicly available fiber spectroscopic data from the Sloan Digital Sky Survey (SDSS), we analyzed nine-strong emission lines of wavelength range 4336 Å to 6739 Å. We find that the strongest emission line is OIII5007, with an intensity of 146.32 × 10-17 erg/s/cm2 /Å. The observed emission lines are well fitted with a Gaussian profile with a coefficient of regression greater than 96%, and the derived full-width half maximum (FWHM) is less than 4.2Å. The Balmer decrement, characterized by the line ratio between Hα and Hβ is 3.07, suggesting a presence of dust at the center of PGC 030133. We derived the star-formation rate and emission line metallicity of PGC 030133 using extinction corrected emission line fluxes. SFR derived from Hα emission line flux is 0.0033 Mʘyear-1 and emission line metallicity derived from flux ratio between NII and Hα is 8.13 dex. Using the SDSS, g, and z-band imaging data, we derived morphological parameters. PGC 030133 has a half-light radius of 3.38 arc second and 3.05 arc second in g-band and z-band respectively and observed one-dimensional light profile is well fitted with a Sersic function with near exponential Sersic index ~ 0.9.